Analisis Pengembangan Usaha Mikro, Kecil Dan Menengah (UMKM) Berbasis Ekonomi Kreatif Di Kabupaten Mamuju - Halim, Abdul (LPPM Universitas Muhammadiyah Mamuju, 2022)
The objectives of this study are 1. To find out the growth of creative economy-based UMKM in Mamuju Regency, 2. To find out the development of creative economy-based UMKM in Mamuju Regency. This study uses types and data sourced from qualitative data and quantitative data. Legitimacy analysis is an analysis conducted to determine the credibility test. According to Sugiono (2012; 121) that